Effect of solvent system on extractability of lipidic components of Scenedesmus obliquus (M2-1) and Gloeothece sp. on antioxidant scavenging capacity thereof - F. Xavier Malcata (2015)
Microalgae are well known for their biotechnological potential, namely with regard to bioactive lipidic componentsespecially carotenoids and polyunsaturated fatty acids (PUFA), well-known for therapeutic applications based on their antioxidant capacity. The aim of this work was to evaluate the influence of four distinct food-grade solvents upon extractability of specific lipidic components, and on the antioxidant capacity exhibited against both synthetic (2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS+)) and biological reactive species (O2- and NO-). A eukaryotic microalga (Scenedesmus obliquus (M2-1)) and a prokaryotic one (Gloeothece sp.) were used as case studies. Concerning total antioxidant capacity, the hexane:isopropanol (3:2) and acetone extracts of Sc. obliquus (M2-1) were the most effective against DPPH and ABTS+, respectively. Gloeothece sp. ethanol extracts were the most interesting scavengers of O2-, probably due the high content of linolenic acid. On the other hand, acetone and hexane:isopropanol (3:2) extracts were the most interesting ones in NO- assay. Acetone extract exhibited the best results for the ABTS assay, likely associated to its content of carotenoids, in both microalgae. Otherwise, ethanol stood out in PUFA extraction. Therefore, profiles of lipidic components extracted are critical for evaluating the antioxidant performancewhich appears to hinge, in particular, on the balance between carotenoids and PUFAs.